Physiological and Clinical Assessment of Resting Physiological Indexes: Resting Full-Cycle Ratio, Diastolic Pressure Ratio, and Instantaneous Wave-Free Ratio. Issue 7 (12th February 2019) - Lee, Joo Myung; Choi, Ki Hong; Park, Jonghanne; Hwang, Doyeon; Rhee, Tae-Min; Kim, Jinseob; Park, Jinhyoung; Kim, Hyung Yoon; Jung, Hae Won; Cho, Yun-Kyeong; Yoon, Hyuck-Jun; Song, Young Bin; et al.
Abstract : Background: Recently, resting pressure–derived indexes such as resting full-cycle ratio (RFR) and diastolic pressure ratio (dPR) have been introduced to assess the functional significance of epicardial coronary stenosis. The present study sought to investigate the agreement of RFR or dPR with other pressure-derived indexes (instantaneous wave-free ratio [iFR] or fractional flow reserve), the sensitivity of RFR or dPR for anatomic or hemodynamic stenosis severity, and the prognostic implications of RFR or dPR compared with iFR Methods: RFR and dPR were calculated from resting pressure tracings by an independent core laboratory in 1024 vessels (435 patients). The changes in resting physiological indexes according to diameter stenosis were compared among iFR, RFR, and dPR. Among 115 patients who underwent 13 N-ammonia positron emission tomography, the changes in those indexes according to basal and hyperemic stenosis resistance and absolute hyperemic myocardial blood flow were compared. The association between resting physiological indexes and the risk of 2-year vessel-oriented composite outcomes (a composite of cardiac death, vessel-related myocardial infarction, and vessel-related ischemia-driven revascularization) was analyzed among 864 deferred vessels. Results: Both RFR and dPR showed a significant correlation with iFR ( R =0.979, P <0.001 for RFR; and R =0.985, P <0.001 for dPR), which was higher than that with fractional flow reserve ( R =0.822, P <0.001; and R =0.819, P <0.001, respectively). RFR and dPR showed a very high agreement with iFR (C index, 0.987 and 0.993). Percent difference of iFR, RFR, and dPR according to the increase in anatomic and hemodynamic severity was almost identical. The diagnostic performance of iFR, RFR, and dPR was not different in the prediction of myocardial ischemia defined by both low hyperemic myocardial blood flow and low coronary flow reserve by 13 N-ammonia positron emission tomography. All resting physiological indexes showed significant association with the risk of 2-year vessel-oriented composite outcomes (iFR per 0.1 increase: hazard ratio, 0.514 [95% CI, 0.370–0.715], P <0.001; RFR per 0.1 increase: hazard ratio, 0.524 [95% CI, 0.378–0.725], P <0.001; dPR per 0.1 increase: hazard ratio, 0.587 [95% CI, 0.436–0.791], P <0.001) in deferred vessels. Conclusions: All resting pressure–derived physiological indexes (iFR, RFR, and dPR) can be used as invasive tools to guide treatment strategy in patients with coronary artery disease. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01621438. Abstract : Supplemental Digital Content is available in the text.